Solve:
|x - 4| = 2

Question

Asked 4/30/2012 8:30:14 AM

Updated 7/23/2014 12:09:54 PM

3 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by andrewpallarca [7/23/2014 12:09:54 PM]

s

Sunshiineluv|Points 658|

theresearcher|Points 2086|

theresearcher|Points 2086|

theresearcher|Points 2086|

Question

Asked 4/30/2012 8:30:14 AM

Updated 7/23/2014 12:09:54 PM

3 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by andrewpallarca [7/23/2014 12:09:54 PM]

Rating

8

|x - 4| = 2;

x - 4 = 2; x = 2 + 4; x = 6

-(x - 4) = 2; -x + 4 = 2; -x = 2 - 4; -x = -2; x = 2

x = 6 or x = 2

x - 4 = 2; x = 2 + 4; x = 6

-(x - 4) = 2; -x + 4 = 2; -x = 2 - 4; -x = -2; x = 2

x = 6 or x = 2

Added 7/23/2014 12:07:52 PM

This answer has been confirmed as correct and helpful.

8

|2x – 7| = 3;

2x - 7 = 3; 2x = 3 + 7; 2x = 10; x = 10/2; x = 5;

-(2x – 7) = 3; -2x + 7 = 3; -2x = 3 - 7; -2x = -4; x = -4/-2; x = 2

x = 5 or x = 2

2x - 7 = 3; 2x = 3 + 7; 2x = 10; x = 10/2; x = 5;

-(2x – 7) = 3; -2x + 7 = 3; -2x = 3 - 7; -2x = -4; x = -4/-2; x = 2

x = 5 or x = 2

Added 7/23/2014 12:09:49 PM

This answer has been confirmed as correct and helpful.

5

Question on: One computer printer can print a company's mailing labels in 40 minutes. A second printer would take 60 minutes to print the labels. How long would it take the two printers, operating together, to print the labels?

It will take 24 minutes to the two printers, operating together, to print the labels.

Solution:

Let x= time it takes both computers working together

Then both computers print at the rate of 1/x mailing labels per min

First computer prints at the rate of 1/40 mailing labels per min

Second computer prints at the rate of 1/60 mailing labels per min

So:

1/40 + 1/60 = 1/x multiply each term by 120x

3x+2x=120

5x=120

x=24 min- - - - -time required when both computers work together

CK

In 24 min first computer completes (1/40)*24=24/40 of the mailing labels

It will take 24 minutes to the two printers, operating together, to print the labels.

Solution:

Let x= time it takes both computers working together

Then both computers print at the rate of 1/x mailing labels per min

First computer prints at the rate of 1/40 mailing labels per min

Second computer prints at the rate of 1/60 mailing labels per min

So:

1/40 + 1/60 = 1/x multiply each term by 120x

3x+2x=120

5x=120

x=24 min- - - - -time required when both computers work together

CK

In 24 min first computer completes (1/40)*24=24/40 of the mailing labels

Added 3/23/2013 7:25:15 PM

Is the algebraic expression a polynomial? If so, give its degree.
9x3 + 6x6 + 8

Question

Updated 6/28/2014 2:59:45 PM

1 Answer/Comment

9x^3 + 6x^6 + 8 is a polynomial with a degree of 6.

Added 6/28/2014 2:59:44 PM

This answer has been confirmed as correct and helpful.

(3x – 1)(2x + 5) **Weegy:** 5x. **User:** (5x – 3y)2 **Weegy:** 31/8 and 25/8 **User:** Perform the indicated operations and simplify.
5x – 4x[8 – 3(x – 2)]
**User:** Factor completely relative to the integers.
49a2b – b3
(More)

Question

Updated 7/1/2014 11:45:46 PM

19 Answers/Comments

jeifunk,

I really dont mind it, either. I beleive incorrect answers MUST BE CORRECTED. Otherwise later incoming auto answers for the same question will still remain incorrect. But i think rules should be the same to all of us, and it seems that you guys (moderators) hold several different opinions on some issues, just a little bit though.

I really dont mind it, either. I beleive incorrect answers MUST BE CORRECTED. Otherwise later incoming auto answers for the same question will still remain incorrect. But i think rules should be the same to all of us, and it seems that you guys (moderators) hold several different opinions on some issues, just a little bit though.

Added 7/1/2014 8:05:14 PM

yeah but if the solution is 5x - 56x - 12x^2, the answer should be -12x^2-51x, its just confusing.

For typos, please delete the answer and ask the expert to add the correct one.

For typos, please delete the answer and ask the expert to add the correct one.

Added 7/1/2014 8:06:39 PM

yeswey, I am just confused on the links you were sending, but I'm pretty sure that we are not supposed to flag answers that has clear typos, we are also not supposed to add a new answer. That's because we still don't have EDIT buttons on the archive to fix any typos.

The thing is, you have already flagged the answer and add a new one before the expert could even fix his/her typos. You should post a link to the expert's feed and let him/her know.

I also forgot to tell you to delete your own typo and add a new one, but don't duplicate answers. That's all.

The thing is, you have already flagged the answer and add a new one before the expert could even fix his/her typos. You should post a link to the expert's feed and let him/her know.

I also forgot to tell you to delete your own typo and add a new one, but don't duplicate answers. That's all.

Added 7/1/2014 8:19:24 PM

Sorry for the typo. I'll just delete it. I won't add the correct one since yeswey has done it for me. I'd be careful next time when answering a math question. Maybe I was just sleepy that time and made a mistake with the sign. Thanks.

Added 7/1/2014 8:26:45 PM

9x + 8 = 2x + 8
**Weegy:** 9x + 8 = 2x + 8,
9x - 2x = 8 - 8
7x = 0
x = 0/7
x = 0
(More)

Question

Expert Answered

Updated 6/16/2014 2:11:11 PM

0 Answers/Comments

Multiply and simplify.
(3x – 1)(2x + 5)
A. 6x2 – 13x – 5
B. 6x2 – 17x – 5
C. 6x2 + 13x – 5
D. 6x2 + 17x – 5

Question

Not Answered

Updated 6/16/2014 2:10:48 PM

1 Answer/Comment

(3x – 1)(2x + 5)

= 6x^2 + 15x - 2x - 5

= 6x^2 + 13x - 5

= 6x^2 + 15x - 2x - 5

= 6x^2 + 13x - 5

Added 6/16/2014 2:10:48 PM

This answer has been confirmed as correct and helpful.

Multiply and simplify:
(3x2 – 2x – 1)(x2 + x + 5)
A. 3x4 + 2x3 + 12x2 – 11x – 5
B. 3x4 + x3 + 12x2 – 10x – 5
C. 3x4 + x3 + 12x2 – 11x – 5
D. 3x4 + x3 + 14x2 – 11x – 5

Question

Updated 7/13/2014 1:57:28 PM

1 Answer/Comment

(3x^2 – 2x – 1)(x^2 + x + 5)

= 3x^4 - 2x^3 + 3x^3 - x^2 - 2x^2 + 15x^2 - x - 10x - 5

= 3x^4 + x^3 + 12x^2 - 11x - 5

= 3x^4 - 2x^3 + 3x^3 - x^2 - 2x^2 + 15x^2 - x - 10x - 5

= 3x^4 + x^3 + 12x^2 - 11x - 5

Added 7/13/2014 1:57:28 PM

This answer has been confirmed as correct and helpful.

34,194,446

questions answered

There are no comments.